Pengelolaan Sumberdaya Ikan Kakap Putih (Lates calcarifer, Bloch, 1790) Berdasarkan Karakter DNA Mitokondria di Perairan Pesisir Kabupaten Merauke - Dandi Saleky; Astaman Amir (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Barramundi (Lates calcarifer, Bloch, 1790) also known as  barramundi has high commercially important. Its utilization is not limited to meat, but also the swim bladder it produces. Knowledge of the genetic aspects of barramundi (Lates calcarifer, Bloch, 1790) is very important in designing genetic improvement and conservation activities for this fish. The purpose of this study was to identify the species of barramundi collected from Pesisir Pantai Payum, Merauke Regency using the Cytochrome Oxidase I gene. DNA extraction used the Blood & Tissue Kit (Qiagen Kit), while the primers used for molecular identificationthe primers were FISH-F1 (5’- TCA ACC AAC CAC AAA GAC ATT GGC AC -3’) and FISH-R1 (5’- TAG ACT TCT GGG TGG CCA AAG AAT CA -3’). The results of this study indicated that the samples collected were barramundi species (Lates calcarifer, Bloch, 1790) with a similarity of 99.61-100% with 9 point mutations. Genetic distance and the level of similarity of DNA sequences greatly determine the formation of a phylogenetic tree. Molecular approaches can be used in the management and conservation of economically important fish species, especially barramundi (Lates calcarifer, Bloch, 1790).